2020
DOI: 10.1186/s12915-020-0747-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane and synaptic defects leading to neurodegeneration in Adar mutant Drosophila are rescued by increased autophagy

Abstract: Background: In fly brains, the Drosophila Adar (adenosine deaminase acting on RNA) enzyme edits hundreds of transcripts to generate edited isoforms of encoded proteins. Nearly all editing events are absent or less efficient in larvae but increase at metamorphosis; the larger number and higher levels of editing suggest editing is most required when the brain is most complex. This idea is consistent with the fact that Adar mutations affect the adult brain most dramatically. However, it is unknown whether Drosoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 72 publications
(96 reference statements)
0
23
0
Order By: Relevance
“…Previous analyses have suggested that hybridization events can generate discordance between species and mitochondrial phylogenies in yeast ( Peris et al. 2017 ; De Chiara et al. 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous analyses have suggested that hybridization events can generate discordance between species and mitochondrial phylogenies in yeast ( Peris et al. 2017 ; De Chiara et al. 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…An additional way whereby innate immune induction could contribute to all Adar 5G1 mutant phenotypes is described in a related manuscript 50 . That manuscript shows that reduced autophagy in Adar 5G1 leads to synaptic defects with aberrant accumulation of neurotransmitter synaptic vesicles and associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Later, ADAR1 was lost in some metazoans, such as arthropods, including Drosophila [45]; Drosophila Adar site-specifically edits many central nervous system (CNS) transcripts and is an orthologue of mammalian ADAR2, which has no known effect on innate immunity and instead site-specifically edits transcripts encoding glutamate receptor subunits to recode them [45]. Adar 5G1 -null mutant flies have severe locomotion defects and aberrant neurotransmitter synaptic vesicle accumulation and develop age-dependent neurodegeneration [46,47]. Unexpectedly, the Drosophila Adar 5G1 mutant also has an aberrant induction of innate immune transcripts caused by loss of RNA editing.…”
Section: Other Adar1 Effects On Innate Immunitymentioning
confidence: 99%